Cross-kingdom interaction between Candida albicans and oral bacteria - Du, Qian; Ren, Biao; Zhou, Xuedong; Zhang, Ling; Xu, Xin (Frontiers in Microbiology, 2022)
Candida albicans is a symbiotic fungus that commonly colonize on mucosal surfaces and mainly affects immuno-compromised individuals. Polymicrobial interactions between C. albicans and oral microbes influence the cellular and biochemical composition of the biofilm, contributing to change clinically relevant outcomes of biofilm-related oral diseases, such as pathogenesis, virulence, drug and host resistance. Notably, the symbiotic relationships between C. albicans and oral bacteria have been well documented in dental caries, oral mucositis, endodontic and periodontal diseases and oral cancer. C. albicans interacts with co-existing oral bacteria through physical attachment, extracellular signals and metabolic cross-feeding. This review discusses the bacterial-fungal interactions between C. albicans and different oral bacteria, with a particular focus on the underlying mechanism and its relevance to the development and clinical management of oral diseases.